Pendidikan Multikultural di Sekolah Umum Berbasis Kampung Santri: Studi di SMPN 1 Arjawinangun Cirebon - Noval Maliki (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2023)
This article presents the results of research on multicultural education at SMPN 1 Arjawinangun. This school is quite interesting in terms of its geographical location and the demographics of its inhabitants. This school does not stand in the middle of the city or suburbs, but instead in the outskirts of the district which usually has a homogeneous society. However, Arjawinangun is different in that around the school there are four large houses of worship of four different religions; Islam, Catholicism, Christianity and Buddhism. The method used is qualitative with interviews and observations as techniques to obtain primary data. The results show that multicultural education in this school does not only occur at the subject level or in the classroom, but is implemented starting from school policies to interactions between individuals (students) in it. It is hoped that with this research, multicultural education in other schools can apply the methods used at SMPN 1 Arjawinangun so that students can have a moderate and tolerant perspective on different beliefs..Â Keywords: Multicultural Education, SMPN 1 Arjawinangun, Santri Village.Â  Â